Analysis of Factors Influencing the Completeness of the MCH Handbook Document as an Early Detection of High-Risk Trimester III Pregnant Women by a Midwife in West Kotawaringin - Siti Zakiah; Byba Melda Suhita; Yenny Puspitasari (Journal for Quality in Public Health, 2021)
The MCH Handbook is a tool for early detection of maternal and child health problems, guiding officers to document properly and correctly. The purpose of this study was to determine the effect of knowledge, workload, availability of tools and facilities, monitoring and evaluation of the Coordinating Midwife on completeness of MCH book documentation for mothers. Third trimester of pregnancy in West Kotawaringin. Method: Quantitative Cross Sectional, the population of midwives in 18 health centers and their networks, a sample size of 102 respondents with the Cluster Random sampling technique and the logistic regression statistical test used the backward stepwise (wald) test with significance ≤ (α 0.05) Result: The influence of knowledge significance (0.301) workload (sig 0.647) availability of tools and facilities (sig 0.025), monitoring and evaluation by coordinating midwives (sig 0.035) simultaneously affect the completeness of MCH book documents for pregnant women in the third trimester, the Nagelkerke R Square coefficient is obtained (62.6%,) The MCH book document is influenced by the midwife's knowledge of the MCH handbook, the availability of tools and facilities and monitoring and evaluation by the Coordinating Midwife. The dominant factor that has the most influence is monitoring and evaluation by the coordinating midwife (Exp. B: 6,969).